Seasonal plasticity in insect models: effect of variable temperatures on developmental oucome - Rodrigues, Yara (2020)
"Heritable intra-specific variation is the raw material for evolution by natural selection, which creates inter-specific diversity. This diversity results from the interactions between evolutionary and developmental processes, both shaped by interactions between organisms and their environments. Environmental factors such as temperature, humidity and nutrition can lead to the production of different phenotypic variants, in a process called developmental plasticity. This developmental plasticity can help organisms to cope with environmental heterogeneity; if the effect of environmental conditions on developmental outcome leads to a better match between organisms and their environments. Natural environments can be very complex, (...)"